The Translation of Neapolitan mafia nicknames in the TV series 'Gomorra' into English and Spanish - Laura Cruz García; Matias Vedaschi (Universitat Jaume I. Department of English Studies, 2023)
This study deals with the translation for subtitling and dubbing of a type of Italian expression called contronomi traditionally used by members of the Neapolitan mafia. We have focused on this special kind of nickname used in the Italian series Gomorra to identify and describe the techniques employed in the translation of these meaningful linguistic cultural elements found in the series into English and Spanish. A contrastive analysis of the source text in the Neapolitan dialect and the subtitled version in English and the dubbed version in Spanish of the first season has been carried out. Through this analysis, conclusions could be drawn about the translation tendency regarding the handling of a cultural aspect of the Neapolitan series: the contronomi of the main and secondary characters of this audiovisual product in the two target languages and cultures.